Global warming and the green paradox: a review of adverse effects of climate policies - Van der Ploeg, R; Withagen, C (University of Oxford, 2013)
This article examines the possible adverse effects of well-intended climate policies. A weak Green Paradox arises if the announcement of a future carbon tax or a sufficiently fast rising carbon tax encourages fossil fuel owners to extract reserves more aggressively, thus exacerbating global warming. We argue that such policies may also encourage more fossil fuel to be locked in the crust of the earth, which can offset the adverse effects of the weak Green Paradox. We show that a subsidy on clean renewables has similar weak Green Paradox effects. Green welfare (the complement of environmental damages) drops (i.e., the strong Green Paradox) if the beneficial climate effects of locking up more fossil fuel do not outweigh the short-run weak Green Paradox effects. Neither the weak nor the strong Green Paradox occurs for the first-best Pigouvian carbon tax. We also pay attention to dirty backstops, spatial carbon leakage and green innovation.